Influence of IoT implementation on supply chain performance: role of information integration and decision-making uncertainty - Xue, Yufei; Yates, Nicola; Ghadge, Abhijeet (Emerald, 2026)
Purpose: Implementing Internet of Things (IoT) is fundamental to the digitalisation of modern supply chains. This paper aims to provide a theory-based explanation for the impact of IoT implementation on information integration, decision-making uncertainty and hence supply chain performance. Design/methodology/approach: This study adopts a qualitative multiple-case study approach to investigating three fast-fashion supply chains in China through 30 semi-structured interviews. Findings: The findings demonstrate that IoT is implemented in the information collection, selection and sharing processes of information integration. Implementing firm-level information collection and selection processes impacts information quality and is linked to environmental uncertainty. Whereas implementation in the supply chain level information sharing process impacts information accuracy and efficiency and is linked to industry uncertainty. Research limitations/implications: This research advances the theoretical understanding of IoT’s role in supply chain management through a two perspective Information Processing Theory-based framework, capturing the mechanisms which underpin the interactions between IoT-enabled information integration and decision-making uncertainty and resultant impact on performance. Practical implications: This research provides a road map for supply chain managers demonstrating how IoT implementation in information integration processes within the firm can improve operational performance. However, when this implementation progresses to supply chain level information-sharing processes, management costs improvements are ultimately realised. Originality/value: This study contributes an empirical, evidence-based explanation of the impact of IoT implementation on supply chain performance. Case study evidence from firms in the early and middle stages of IoT implementation reveal that the mechanisms governing the interactions between information integration, decision-making uncertainty and their impact on performance are fundamentally different for firm and supply chain IoT implementation processes. It is only in implementing the information sharing process at the supply chain level that cost benefits are achieved.
Keywords: Internet of Things; Supply chain performance; Information integration; Decision-making uncertainty; Information processing theory; 35 Commerce, Management, Tourism and Services; 8.1 Organisation and delivery of services; 9 Industry, Innovation and Infrastructure; Business & Management; 3507 Strategy, management and organisational behaviour; 3509 Transportation, logistics and supply chains